Teachers' Efforts in Developing the Moral Intelligence of Elementary School Children Through Citizenship Education Learning - Anggita, Dian Giska (International Journal of Students Education, 2024)
This study aims to explore the role of Civic Education teachers in developing students' moral intelligence at the elementary school level. In the context of increasingly complex education in the era of globalization, it is important for educators to not only focus on academic aspects, but also on the formation of students' character and morals. The method used in this study is qualitative with a literature study approach, which involves analyzing various sources of literature, including books, articles, and journals that are relevant to the topic discussed. The results of the study indicate that teachers have a central role as agents of change in moral education. Through the integration of moral values in the Civic Education curriculum, teachers can create a learning environment that supports the development of students' character. This study identifies several effective strategies, such as the implementation of character education, role models shown by teachers, and the use of interactive and thematic learning methods